THE IMPACT OF SOROGAN AND BANDONGAN METHODS ON MAHASANTRI'S PROFICIENCY IN READING THE YELLOW BOOKS - Ilzam Hubby Dzikrillah Alfani; Mukhsin, Mukhsin; Anggi Anggraini; Ana Dwi Lestari (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2025)
This study aims to identify the impact of two learning methods (sorogan and bandongan) used in the H Mahasantri Complex of Krapyak Islamic Boarding School, Ali Maksum Foundation Yogyakarta. Aiming to find out which learning method is very significant to the ability of Mahasantri to read the yellow book. This research is qualitative in nature with the type of interview study research, the data is analyzed descriptively assisted by written references. This study concludes that the sorogan method and the bandongan method have their own characteristics and uses. in terms of the ability to read the yellow book of Mahasantri, the sorogan method is favored because this method can provide more effective learning. There are many profound positive impacts on the student's scientific development, independence, discipline, and spirituality. The sorogan and bandongan methods can be combined with the aim of improving the quality of education by providing a balance between individual deepening and collective understanding. By combining the two methods, students can learn in more diverse ways, gain a deeper understanding, and overcome the shortcomings that exist in each method.